Reflections on the Establishment of a Risk Control and Supervision and Inspection Mechanism for Water Safety Production - Sheng, Huibo (International Journal of Social Sciences and Public Administration, 2025)
The new development concept puts forward higher requirements for the construction of water safety production management system. By analyzing the characteristics of water safety production, it puts forward the optimization plan of risk pre-control system and establishes a systematic risk management and control system. Based on the improvement of the policy implementation mechanism and the construction of the supervision and inspection system, the whole process safety management closed loop is formed. The research results are of great significance in enhancing the level of safe production management in the water industry, guaranteeing the safe operation of water facilities, and providing theoretical guidance for the practice of safety management in water enterprises.